Al-Tadamun partnership - Ibrahim, Yahya Mohammed Al- Amin Al- Hassan (Arab Journal for Sciences and Research Publishing, 2016)
This research discuss the partnership company, its legal role, after basic properties statement of partnership company, which are: 1 – partners in the partnership company are responsible completely for all company commitments, partners are consider in the center of combined sponsorships for the company, the rest of partners have to pay on behalf of them and bare the loss from their own money. 2 – it’s not allowed to negotiate partner’s share and he can’t transfer it to others without confirmation from other partners, this is a general rule , doesn’t relate to general regulations , so partners can make an agreement includes transferring the share to others . 3 – the partner consider as a merchant as soon as company establishing, if the company is an partnership trading company, he must be qualified to trade, that means that he is more than 21 years old or reached 18 years old , and he has to get a permission from the primary court , the banned people which are prohibited to trade , they can’t be a combined partners . 4 –the partnership company can has one brand name or more from the combined partners followed by “and his partners “ or “ their partners” , it’s not necessary the brand name for the company to be for all partners specially if they are too many , if the company has no brand name so all partners will sign by their own signature . After checking the partnership company, we find that it’s legal because it matches most of companies regulations in the Islamic jurisprudence, and it’s different in some formalities , because it’s a mix from bargaining company and Al-Anan company , it’s agree with bargaining company in solidarity principle among partners , and agree with Anan company in capital share equality for all partners .